Management model for the integration of virtual reality and augmented reality as didactic tools: Case Colegio Técnico Profesional de Nicoya - Stefan Obando Zambrano, Beyker (2024)
This research aims to present a management model for the incorporation of virtual reality and augmented reality technologies at the Colegio Técnico Profesional de Nicoya. This model seeks to facilitate the effective integration of these tools into the educational environment by considering essential aspects for their successful implementation. The research is based on a descriptive and quantitative approach. Surveys were conducted with 306 students during the first quarter of 2023 to identify the subjects most suitable for applying these technologies and to gather information on the availability of electronic devices and the quality of Internet connectivity both at the educational institution and in students' homes. Furthermore, the research highlights the need to involve all stakeholders in the process, including teachers, students, and administrative staff. Continuous evaluation of technology use will allow for adjustments to strategies and maximize their effectiveness, thus ensuring that the proposed educational objectives are achieved and enhancing the learning experience.